Schizophrenia Increases Variability of the Central Antioxidant System: A Meta-Analysis of Variance From MRS Studies of Glutathione - Palaniyappan, Lena; Sabesan, Priyadharshini; Li, Xuan; Luo, Qiang (Frontiers in Psychiatry, 2021)
Patients with schizophrenia diverge in their clinical trajectories. Such diverge outcomes may result from the resilience provided by antioxidant response system centered on glutathione (GSH). Proton Magnetic Resonance Spectroscopy (1H-MRS) has enabled the precise in vivo measurement of intracortical GSH; but individual studies report highly variable results even when GSH levels are measured from the same brain region. This inconsistency could be due to the presence of distinct subgroups of schizophrenia with varying GSH levels. At present, we do not know if schizophrenia increases the interindividual variability of intracortical GSH relative to matched healthy individuals. We reviewed all 1H-MRS GSH studies in schizophrenia focused on the Anterior Cingulate Cortex published until August 2021. We estimated the relative variability of ACC GSH levels in patients compared to control groups using the variability ratio (VR) and coefficient of variation ratio (CVR). The presence of schizophrenia significantly increases the variability of intracortical GSH in the ACC (logVR = 0.12 ; 95% CI: 0.03–0.21; log CVR = 0.15; 95% CI = 0.06-0.23). This meta-analytical finding supports the existence of subtypes with varying GSH levels in schizophrenia (redox-deficient and redox-sufficient groups). An increase in GSH variability reflects reduced predictability of the adaptive antioxidant response when patients face increased oxidative stress. Uncovering the origins of this illness-specific reduction in the redox system stability may provide novel treatment targets in schizophrenia.